Penegakan Hukum Bagi Pelaku Pencemaran di Sungai Badung Denpasar - I Putu Satria Adhi Darma; I Nyoman Gede Sugiartha; Ketut Adi Wirawan (Jurnal Analogi Hukum, 2024)
There is so much accumulation of waste every day that this has the potential to increase as the population increases. Waste is a major problem seen from the development of population, so policies are needed to overcome this, one of which is the policy of managing households. The formulation of the problems in this study are How is law enforcement against the perpetrators of pollution in the Badung river Denpasar? What factors are the obstacles in law enforcement against pollution of the Badung Denpasar river basin? The research method used is empirical legal research with field data as the main data source, such as the results of interviews and observations. There is a need for cooperation between DLHK and village officials to carry out socialization to the community regarding the impact of garbage pollution due to garbage disposal, as well as the participation of traditional interpreters in terms of addressing issues about garbage by urging people not to directly throw their garbage into the river.